ROS of Distinct Sources and Salicylic Acid Separate Elevated CO2-Mediated Stomatal Movements in Arabidopsis - He, Jingjing; Zhang, Ruo-Xi; Kim, Dae Sung; Sun, Peng; Liu, Honggang; Liu, Zhongming; Hetherington, Alistair M.; Liang, Yun-Kuan (Frontiers in Plant Science, 2020)
Elevated CO2 (eCO2) often reduces leaf stomatal aperture and density thus impacts plant physiology and productivity. We have previously demonstrated that the Arabidopsis BIG protein distinguishes between the processes of eCO2-induced stomatal closure and eCO2-inhibited stomatal opening. However, the mechanistic basis of this action is not fully understood. Here we show that eCO2-elicited reactive oxygen species (ROS) production in big mutants was compromised in stomatal closure induction but not in stomatal opening inhibition. Pharmacological and genetic studies show that ROS generated by both NADPH oxidases and cell wall peroxidases contribute to eCO2-induced stomatal closure, whereas inhibition of light-induced stomatal opening by eCO2 may rely on the ROS derived from NADPH oxidases but not from cell wall peroxidases. As with JA and ABA, SA is required for eCO2-induced ROS generation and stomatal closure. In contrast, none of these three signals has a significant role in eCO2-inhibited stomatal opening, unveiling the distinct roles of plant hormonal signaling pathways in the induction of stomatal closure and the inhibition of stomatal opening by eCO2. In conclusion, this study adds SA to a list of plant hormones that together with ROS from distinct sources distinguish two branches of eCO2-mediated stomatal movements.